Evaluating the Efficacy of Clerodendrum minahassae Ethanol Extract on Insulin Regulation in Diabetic Wistar Rats - Rumangu, Chrisa P.; Fatimawali, Fatimawali; Manampiring, Aaltje Ellen; Kepel, Billy Johnson; Budiarso, Fona Dwiana Hermina; Bodhi, Widdhi (Heca Sentra Analitika, 2024)
Leilem plant (Clerodendrum minahassae Teisjm & Binn.) from the genus Clerodendrum has the potential as antidiabetic, antihypertensive, anti-inflammatory, antioxidant, antimalarial, antitumor, antidiarrheal, antimicrobial and antihyperlipidemic. This study aimed to see the effect of ethanol extract of Clerodendrum minahassae (CM) leaves on increasing insulin levels in diabetic Wistar rats induced with streptozotocin. This study was conducted in vivo, using 20 rats as experimental animals. The experimental animals were divided into four groups, namely the negative control group (Na-CMC 0.5%), the ethanol extract group of leilem leaves 250 mg and 500 mg, and the positive control group (glibenclamide) as a comparison. Each experimental animal was induced streptozotocin intraperitoneally; then, each solution was given for 14 days according to the test group. After the treatment, the animals were terminated for blood collection; the blood was then centrifuged to obtain blood plasma serum. Blood plasma serum was measured by the ELISA Kit (Rat/Mouse Insulin) method, and then the results were read on a spectrophotometric device. The results of the sample insulin concentration obtained showed that 250 mg/kgBW and 500 mg/kgBW of the CM ethanol extract group could increase insulin levels in diabetic Wistar rats, the same as the positive control group glibenclamide. In contrast, the Na-CMC 0.5% as a negative control group did not show a significant increase in insulin levels. Leilem leaves can be developed for further research on their antidiabetic activity both in vitro, in vivo, and in silico, as well as their toxicity.